Telecommunications liberalization and regulatory governance: lessons from Latin America (2000)
The role of the state changed in Latin American and Caribbean countries between 1985 and 1995 as eight regulatory commissions were created (for the 19 countries in our regional sample). This institutional innovation was part of the liberalization process that has permeated the hemisphere. This study examines the determinants of telephone lines per capita, using economic, institutional and regulatory variables. Lacking information on total investment, we use lines as a proxy for telecommunications investment. The economic variables have the expected impacts. Gross domestic product (GDP) per capita affects investment in a positive way: telecommunications services are income-elastic. Openness (exports plus imports as a percentage of GDP) captures significant external links which require telecommunications to coordinate the production and delivery of goods and services. This variable had a positive (but not statistically significant) impact. Similarly, greater population density was a significant determinant of lines per capita for this particular sample of countries (reflecting lower cost of service for urban areas). Building on the work of Levy and Spiller (Regulations, Institutions, and Commitment: Comparative Studies of Telecommunications, Cambridge University Press, New York, 1996), we introduce institutional indices to capture the effects of political democracy, economic freedom, and a sound regulatory framework. The latter captures the degree of independence of the regulatory body, enforcement powers, neutrality, and mechanisms for resolving conflicts. It might be viewed as a proxy for serious reform initiatives (including reduction of entry barriers and privatization). The regulatory framework and freedom factors have significant positive impacts on telephone lines per capita. Another important explanatory variable is the number of cellular phones per capita. The positive impact is consistent with cellular being a complement for fixed line telephony. Alternatively, the positive impact could reflect a “competition effect” whereby competitive entrants in a liberalized sector stimulate improved performance (and additional investment) by incumbent wire-line firms.